Prove ((cscx-cotx)(cscx+cotx))/secx=cosx

hexacordoK 2021-01-28 Answered
Prove (cscxcotx)(cscx+cotx)secx=cosx
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

Nathanael Webber
Answered 2021-01-29 Author has 117 answers

LHS=csc2xcot2secx(derence of two)
=1/secx(formula 1+cot2x=csc2x,thus cscxcot2x=1)
=cosx=RHS

Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

New questions